Igniting Voices Together: Work in Pairs as a Catalyst for Speaking English Proficiency in EFL Learning - Nurjamin, Lucky Rahayu; Salsabila, Dya; Yuliani, Lia (ELE Reviews: English Language Education Reviews, 2025)
This classroom action research investigates the iteratively refined Work in Pairs strategy to enhance oral English skills among 35 eleventh-grade Sundanese-speaking learners. Employing a two-cycle classroom action research design, the study addressed initial challenges in pronunciation, fluency, and vocabulary. Data collection was comprehensive, utilizing preliminary classroom observations and audio recordings for baseline assessment, then consistently applying speaking performance rubrics, a teacher-researcher reflective journal, and student feedback forms/interviews throughout the cycles. Cycle 1, involving pair-based dialog, yielded modest fluency improvements. Reflection, revealing persistent L1 phonetic interference and vocabulary limitations, led to Cycle 2. This cycle incorporated rearranged pairings, audio listening, and targeted vocabulary lists, resulting in substantial gains across all areas, particularly fluency and pronunciation. The findings demonstrate the efficacy of the Work in Pairs strategy, especially when combined with targeted supplementary materials and iterative adaptation, in fostering holistic oral English proficiency in a multilingual context. This study offers practical insights for educators on using collaborative learning to improve speaking skills.